PENGARUH CORPORATE GOVERNANCE TERHADAP FINANCIAL PERFORMANCE DENGAN MANAGEMENT CONTROL SYSTEM SEBAGAI VARIABEL MEDIASI PADA PERUSAHAAN MANUFAKTUR DI SURABAYA DAN SEKITARNYA - Andreas Christian Hartanto; Devie Devie Devie (Business Accounting Review, 2018)
This research was conducted to find out the influence of corporate governance to financial performance through management control system as intervening variable in the manufacturing company located at Surabaya and the surrounding areas. This study used a qualitative approach, which means the data obtained from respondent at the company filling the questionnaire. The data were obtained from 33 manufacturing company located at Surabaya and the surrounding areas and processed by using SmartPLS software version 3.0. The result showed that there was positive and significant influence of corporate governance toward financial performance and management control system. Management control system had positive and significant influence towards financial performance, and the result also showed that management control system could mediate the affect of corporate governance towards financial performance, but the direct affect showed stronger result than the indirect effectso it meant that the indirect affect was not strong enough.